Special issue: imperfect competition and contemporary macroeconomics. Editor’s introduction - Dixon, Huw David (2018)
This paper introduces the special issue by tracing out the history of imperfect competition in macroeconomics, particularly since 1980. It argues that in the search for a micro-foundation for nominal rigidity it was necessary to abandon the assumption of competitive equilibrium where all agents are price-takers. This led to models where firms and other optimising agents set wages and prices which were part of the new Keynesian economics of the 1980s. When these were combined with quantitative dynamic equilibrium methods it gave rise to the new neoclassical synthesis models which dominate macroeconomics today. The assumption of imperfect competition provides an equilibrium with different properties to the competitive, and one particular focus is on the relationship between the markup and the fiscal multiplier.